Prompting arm activity after stroke: A clinical proof of concept study of wrist-worn accelerometers with a vibrating alert function - Da-Silva, Ruth H; van Wijck, Frederike; Shaw, Lisa; Rodgers, Helen; Balaam, Madeline; Brkic, Lianne; Ploetz, Thomas; Jackson, Dan; Ladha, Karim; Price, Christopher I (Journal of rehabilitation and assistive technologies engineering, 2018)
Background Frequent practice of functional movements after stroke may optimise motor recovery; however, it is challenging for patients to remember to integrate an impaired limb into daily activities. We report the activity responses of stroke patients receiving a vibrating alert delivered by a tri-axial accelerometer wristband to prompt movement of the impaired arm if hourly activity levels fell. Methods Adults with upper limb impairment ≤28 days post-stroke wore the device for four weeks. Therapists and patients reviewed movement activity data twice weekly to agree ongoing rehabilitation activities and programme the wristband with a personalised prompt threshold (median baseline activity + 5%, 25% or 50%). Results: Seven patients completed the programme (five males; mean ± standard deviation (age) 64 ± 5 years; days post-stroke 13 ± 7; baseline/four-week Action Research Arm Test median (Interquartile range (IQR)) 39 (8, 44)/56 (11, 57)). Wristbands were worn for 89% of programme duration. A total of 1,288 prompts were delivered, with a median of four (IQR 3,7) prompts per patient per day. Mean activity increases following a prompt ranged from 11% to 29%. Conclusions Feedback delivered by a programmable accelerometer increased impaired arm activity. Improvements are required in device reliability before conducting a pragmatic clinical trial to examine the impact upon recovery.